Gender Role Orientation with Health Literacy and Self-Efficacy for Healthy Eating among Japanese Workers in Early Adulthood - Hosokawa, Chizuru; Ishikawa, Hirono; Okada, Masafumi; Kato, Mio; Okuhara, Tsuyoshi; Kiuchi, Takahiro (Frontiers in Nutrition, 2016)
Gender role, independent of biological sex, affects health. However, research on healthy eating that considers the importance of gender norms is scarce. People who are androgynous and have high masculinity and femininity are reported to have better health practices than other people. The present study aimed to examine the differences in health literacy and self-efficacy for healthy eating by gender role in Japanese men and women. Participants were 629 men and women aged 25–34 years, recruited via a Japanese Internet research company database. Participants were categorized into four gender role groups using the Japanese Gender Role Index. Health literacy and self-efficacy for healthy eating were assessed using the Healthy Eating Literacy (HEL) scale and the Healthy Eating and Weight Self-Efficacy (HEWSE) scale. Analysis of variance with Bonferroni-adjusted post-hoc tests and hierarchical multiple regression were used to test the research hypotheses. We found that the Androgynous group had significantly higher HEL and HEWSE scores than the Feminine and Undifferentiated groups. The Masculine group scored significantly higher on both measures than the Undifferentiated group. Being Androgynous (HEL: β = 0.34, p < 0.001; HEWSE: β = 0.30, p < 0.001) was a strong predictor for higher scores even after considering other predictors. The results showed significant associations between gender role orientation and individual health literacy and self-efficacy for healthy eating. These findings may be relevant for promoting healthy eating from the perspective of gender norms.